Evaluation of Micro Hardness of Magnesium Alloy Coated with ZnO and Al2O3 - Chandra, Divya; Nathi Ram Chauhan (International Journal of Integrated Engineering, 2024)
Magnesium and its alloys have wide range of application in automobile and aircraft industries because of its excellent mechanical properties i.e. high strength to weight ratio, availability and good castability etc. However, some challenges occur in using magnesium and its alloys in automobiles where the material has to withstand high wear and it has to be hard.  In this work a study has been done on eleven samples of magnesium alloy AZ91 coated with different percentage mixture of ZnO and Al2O3 particles by plasma spray method. Effect of presence of ceramic particles on the surface of substrate was studied. Micro Vickers hardness test was conducted on the samples, and it was found that the hardness of the samples decreases with decreasing percentage of Al2O3 particles. Firstly, the hardness decreases slightly with decreasing percentage of Al2O3 particles and beyond 50% Al2O3 particles composition mixture the hardness decreases rapidly. Result shows that the contribution of Al2O3 particles plays important role in increasing the hardness of coated surface